Hobi Touring Motor sebagai Ruang Pembentukan Identitas Keberagamaan Remaja Muslim: Perspektif Clifford Geertz - Rafi Ahlina Majid (Advances In Education Journal, 2025)
This article examines how the motorcycle touring hobby functions as a formative arena of religious identity for Muslim youth involved in da‘wah-oriented biker communities. Contemporary Muslim youth live amidst popular street culture, digital technology, and hobby-based communities that become crucial spaces for self-expression and identity formation. In this context, several Muslim biker communities consciously integrate touring with da‘wah activities, such as observing the five daily prayers, organizing short study circles, distributing Qur’anic mushaf, and promoting ethical riding and polite communication. This study employs a qualitative–interpretive case study through in-depth interviews, participant and non-participant observation, and documentation. Data are analyzed using thick description and Clifford Geertz’s concept of religion as a system of symbols to interpret visual, verbal, and practical symbols that connect the touring hobby with religious meanings. The findings indicate that motorcycle touring becomes a medium for the internalization of Islamic values, strengthening faith, prayer discipline, control of speech and emotions, solidarity, and the construction of an identity as “Muslim bikers preaching on the road